High-performance composite negative electrode material based on bulk-phase silicon nanocrystals as well as preparation and application of high-performance composite negative electrode material

By using composite negative electrode materials based on bulk silicon nanocrystals in lithium-ion batteries and combining high-temperature disproportionation reaction technology of thermal network materials, the problem of unstable circulation performance caused by volume expansion of silicon-based negative electrode materials is solved, and an efficient, controllable and low-cost modification effect is achieved.

CN119742336AActive Publication Date: 2025-04-01TONGJI UNIV
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411907831.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The silicon-based negative electrode material has unstable cycling performance due to mechanical stress caused by volume expansion in lithium-ion batteries. The existing modification methods are costly, complex in process and high energy consumption.

Method used

High-performance composite anode material based on bulk-phase silicon nanocrystals is used to grind silicon oxide powder, lithium source additives and thermal network materials to conduct high-temperature disproportionation reactions to generate small-sized and high-quality crystalline silicon nanocrystals, and combine thermal network materials to improve heat transfer efficiency.

Benefits of technology

It significantly improves the cycle stability of the material, reduces production costs, simplifies the process, improves the energy utilization rate, and achieves stable charging and discharge under high-rate conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742336A_ABST
    Figure CN119742336A_ABST
Patent Text Reader

Abstract

The invention relates to a bulk phase silicon nanocrystal-based high-performance composite negative electrode material and preparation and application thereof, and the preparation method of the negative electrode material comprises the following steps: (1) weighing silicon monoxide powder, a lithium source additive and a heat conduction network material, grinding and mixing to obtain a precursor mixture; and (2) placing the precursor mixture on a carrier, carrying out high-temperature disproportionation reaction, and cooling to room temperature to obtain modified silicon monoxide composite powder, namely a target product. Compared with the prior art, the preparation method has the advantages that the mechanical stress caused by volume expansion of the nanocrystals in the circulation process can be effectively relieved, and particle breakage is avoided, so that the circulation stability and the like of the material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of silicon-based negative electrode materials, and relates to a high-performance composite negative electrode material based on bulk silicon nanocrystals and the preparation and application thereof. Background Art

[0002] As lithium-ion batteries are widely used in electric vehicles, wearable electronic devices, and various mobile power devices, people's pursuit of their performance is no longer limited to high energy density. In response to today's fast-paced and efficient working and living environment, the future development trend of the new generation of lithium-ion batteries is to be able to work normally and stably increase energy under high-rate rapid charging and discharging conditions.

[0003] Among them, the negative electrode material is one of the important components in the battery, and its inherent specific capacity and structural stability and other physicochemical properties directly determine the electrochemical performance of the entire battery system. Although silicon has a high specific capacity as a negative electrode, the poor cycle performance caused by the huge volume change is the main challenge hindering the commercialization of silicon-based negative electrode materials. Silicon oxide materials have a unique microstructure of random mixing of nanoscale Si and SiO2 phases, which can improve the cycle performance of silicon-based negative electrode materials. At present, various stress dissipation strategies have been adopted for silicon oxide materials to buffer volume expansion, such as designing nanostructures, surface coating, and developing efficient binders. Among them, the production cost and energy consumption of nanostructures are high (such as CN109244386A), the surface coating and chemical etching manufacturing process are complex, the synthesis is uncontrollable and will consume additional energy (such as CN108987732A); and the optimization of binders is expensive and has high environmental costs (such as CN116759581B). Therefore, it is still necessary to develop an efficient, controllable and low-cost method for modifying silicon oxide negative electrodes. Summary of the invention

[0004] The purpose of the present invention is to provide a high-performance composite negative electrode material based on bulk silicon nanocrystals and its preparation and application, which can obtain silicon nanocrystals with small size and better crystallization characteristics while maintaining the active state, thereby effectively alleviating the mechanical stress caused by the volume expansion of the nanocrystals during the cycle, avoiding particle rupture, and significantly improving the cycle stability of the material. In addition, the present invention greatly improves the Joule heat transfer efficiency by introducing a thermal conductive network material, and further optimizes the energy utilization rate of the rapid heating and cooling heat treatment process.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] In one aspect, the present invention provides a method for preparing a high-performance composite negative electrode material based on bulk silicon nanocrystals, comprising the following steps:

[0007] (1) weighing silicon oxide powder, lithium source additive and thermal conductive network material, grinding and mixing to obtain a precursor mixture;

[0008] (2) placing the precursor mixture on a carrier, and performing a high-temperature disproportionation reaction in an inert atmosphere, and cooling to room temperature to obtain a modified silicon oxide composite powder, which is the target product.

[0009] Furthermore, the lithium source additive is selected from one or more of LiOH·H2O, LiH, LiAlH4 and LiBH4. LiOH·H2O is preferred because it is stable at room temperature and has a high safety factor.

[0010] Furthermore, the thermal conductive network material is one or more of carbon nanotubes, boron nitride, diamond or silicon carbide. Carbon nanotubes are preferred. CNTs can make the precursors disperse evenly, overcoming the disadvantage of uneven heat transfer during thermal shock treatment; in addition, the interconnected filler network in CNTs provides more heat transfer channels, greatly improving the Joule heat transfer efficiency.

[0011] Furthermore, the mass ratio of silicon oxide powder, lithium source additive and thermal conductive network material is (10-40):1:(0.05-2), preferably (15-35):1:(0.2-1).

[0012] Furthermore, the particle size of silicon oxide particles is 1 to 20 μm, more preferably, the particle size is 5 μm.

[0013] Furthermore, the grinding and mixing time is 5 to 30 minutes. More preferably, the grinding time is 10 minutes. The solid powder should be ground until it is difficult to distinguish the additive particles with the naked eye.

[0014] Furthermore, the carrier is one of a graphite sheet and a carbon paper.

[0015] Furthermore, the heating method of the high-temperature disproportionation reaction is one or more of laser induced heating, magnetic induction heating, plasma heating, Joule heat thermal shock and microwave heating.

[0016] Furthermore, when the heating method is microwave heating, the power of microwave heating is 900-1800W, and the heating time is 5s-3min;

[0017] When the heating method is Joule heat thermal shock, the number of Joule heat thermal shock treatments is 1 to 10 times, the single time is 0.05 to 5 seconds, the temperature is 700 to 1800° C., and the time interval between two adjacent heatings is about 5 seconds.

[0018] Furthermore, the high temperature disproportionation reaction is carried out under a vacuum environment.

[0019] In a second aspect, the present invention provides a high-performance composite negative electrode material based on bulk silicon nanocrystals, which is prepared based on the preparation method described above.

[0020] In a third aspect, the present invention provides an application of a high-performance composite negative electrode material based on bulk silicon nanocrystals in a negative electrode of a lithium-ion battery.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] 1) The present invention innovatively introduces materials such as lithium hydroxide and carbon nanotubes as disproportionation initiators, wherein lithium hydroxide and other lithium salts can cooperate with thermal shock to promote the formation of disproportionated nano-silicon and increase the crystallinity of the generated nano-silicon, thereby exerting a greater capacity advantage. Materials such as carbon nanotubes can play the role of thermal conductive network and electronic conductive network, which can improve heat transfer efficiency and alleviate volume expansion to a certain extent, which is conducive to maintaining the structural stability of the silicon oxide negative electrode and realizing stable long-term cycle of the silicon oxide negative electrode.

[0023] 2) The silicon oxide preparation equipment of the present invention can adopt heating methods such as Joule heat thermal shock device, which can accurately control and utilize the thermal reaction in time and space dimensions, and is an efficient, low energy consumption, high throughput preparation technology.

[0024] 3) The present invention can regulate the crystal size and crystallinity through different thermal shock temperatures, and obtain silicon nanocrystals with small size and optimal crystallinity in an undeactivated state, which is crucial for alleviating particle expansion and preventing particle crushing, thereby obtaining a more stable cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of the present invention of generating bulk nano-silicon crystals by disproportionation through heat treatment.

[0026] Figure 2 This is the X-ray diffraction pattern of the modified silicon monoxide negative electrode material provided in Example 1 of the present invention.

[0027] Figure 3 This is the XPS spectrum of the silicon 2 oxide negative electrode material before and after modification provided in Comparative Example 1 and Example 1 of the present invention.

[0028] Figure 4 (b, c, d) transmission electron microscope images and (e) selected area electron diffraction images of Comparative Example 1 (a) and Example 1 provided by the present invention.

[0029] Figure 5 The differential capacitance curves of the modified silicon monoxide negative electrode materials provided in Examples 1, 2, 3 and 4 of the present invention.

[0030] Figure 6This is a comparison chart of the cycle performance of the modified silicon 2 oxide negative electrode material provided in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.

[0031] Figure 7 This is a comparison chart of the cycle performance of the modified silicon iodide negative electrode materials provided in Example 1, Example 2, Example 3, Example 4 and Comparative Example 1 of the present invention.

[0032] Figure 8 This is a comparison chart of the rate performance of the modified silicon 2 oxide negative electrode materials provided in Example 1 of the present invention and Comparative Examples 1 and 2.

[0033] Fig. 9 This is a comparison chart of the cycle performance of the modified silicon iodide negative electrode material provided in Example 10, Example 1 and Comparative Example 3 of the present invention.

[0034] Fig.10 This is a comparison chart of the cycle performance of the modified silicon 2 oxide negative electrode material provided in Example 1 of the present invention and Comparative Example 4.

[0035] Fig.11 This is a comparison chart of the cycle performance of the modified silicon 2 oxide negative electrode material provided in Example 1 of the present invention and Comparative Example 5. DETAILED DESCRIPTION

[0036] The present invention discloses a modification and preparation method of silicon oxide negative electrode material. The main synergistic precursors of the material include lithium hydroxide and carbon nanotubes. The most preferred heat treatment conditions are found by optimizing the Joule heat thermal shock temperature, time and frequency to obtain controllable generation of disproportionate silicon nanocrystals with strong crystallinity and small size.

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified, for example, carbon nanotubes were purchased from Shenzhen Defang Nanotechnology Co., Ltd., CN-10302.

[0039] Embodiment 1:

[0040] The preparation method of disproportionated silicon dioxide in this embodiment comprises the following steps:

[0041] S1. Weigh 0.3 g of silicon dioxide, 0.015 g of lithium hydroxide and 0.003 g of carbon nanotubes in a mass ratio of 100:5:1, place them in a mortar and grind them for 10 min to mix them evenly to obtain a precursor;

[0042] S2. Place the precursor on the carrier carbon paper of the Joule heat shock device, connect it to the positive electrode and the negative electrode respectively through wires, vacuum treat for 10 minutes, turn on the power supply in the Joule heat treatment device, set the current to 200A, and the voltage to 40V, and perform high-temperature heat shock treatment on the precursor on the carbon paper. The single heat shock treatment time is 0.1s, the number of heat shock treatments is 3 times, the time interval between two adjacent heat shocks is 5s, and the temperature of the Joule heat shock treatment is 1200°C to obtain disproportionated silicon dioxide.

[0043] The disproportionate silicon oxide prepared in this example was subjected to XRD detection, and the detection spectrum is shown in Figure 1 The XRD spectrum of Example 1 shows that there is a Si peak, which is relatively sharp, indicating that the preparation method of this example achieves the occurrence of disproportionation reaction. In addition, TEM characterization is performed on this example, and the morphology spectrum is shown in Figure 2 ,The TEM spectrum of Example 1 shows that silicon nanocrystals with an average size of about 2 nm and good crystallinity are obtained.

[0044] Example 2

[0045] The preparation method of disproportionated silicon dioxide in this embodiment comprises the following steps:

[0046] S1. Weigh 0.3 g of silicon dioxide, 0.015 g of lithium hydroxide and 0.003 g of carbon nanotubes in a mass ratio of 100:5:1, place them in a mortar and grind them for 10 min to mix them evenly to obtain a precursor;

[0047] S2. The precursor is placed on a carrier carbon paper of a Joule heat shock device, connected to a positive electrode and a negative electrode respectively through wires, and subjected to vacuum treatment for 10 minutes. The power supply in the Joule heat treatment device is turned on, the current is set to 200A, and the voltage is set to 40V. The precursor on the carbon paper is subjected to Joule heat shock treatment. The single heat shock treatment time is 0.1s, the number of heat shock treatments is 3 times, and the temperature of the Joule heat shock treatment is 1100°C to obtain disproportionated silicon dioxide.

[0048] Example 3

[0049] The preparation method of disproportionated silicon dioxide in this embodiment comprises the following steps:

[0050] S1. Weigh 0.3 g of silicon dioxide, 0.015 g of lithium hydroxide and 0.003 g of carbon nanotubes in a mass ratio of 100:5:1, place them in a mortar and grind them for 10 min to mix them evenly to obtain a precursor;

[0051] S2. The precursor is placed on a carrier carbon paper of a Joule heat shock device, connected to a positive electrode and a negative electrode respectively through wires, and subjected to vacuum treatment for 10 minutes. The power supply in the Joule heat treatment device is turned on, the current is set to 200A, and the voltage is set to 40V. The precursor on the carbon paper is subjected to Joule heat shock treatment. The single heat shock treatment time is 0.1s, the number of heat shock treatments is 3 times, and the temperature of the Joule heat shock treatment is 1000°C to obtain disproportionated silicon dioxide.

[0052] Example 4

[0053] The preparation method of disproportionated silicon dioxide in this embodiment comprises the following steps:

[0054] S1. Weigh 0.3 g of silicon dioxide, 0.015 g of lithium hydroxide and 0.003 g of carbon nanotubes in a mass ratio of 100:5:1, place them in a mortar and grind them for 10 min to mix them evenly to obtain a precursor;

[0055] S2. The precursor is placed on a carrier carbon paper of a Joule heat shock device, connected to a positive electrode and a negative electrode respectively through wires, and subjected to vacuum treatment for 10 minutes. The power supply in the Joule heat treatment device is turned on, the current is set to 200A, the voltage is set to 40V, and the precursor on the carbon paper is subjected to heat shock treatment. The single heat shock treatment time is 2s, the number of heat shock treatments is 2 times, and the temperature of the Joule heat shock treatment is 1600°C to obtain disproportionated silicon dioxide.

[0056] Example 5

[0057] The preparation method of disproportionated silicon dioxide in this embodiment comprises the following steps:

[0058] S1. Weigh 0.3 g of silicon dioxide, 0.015 g of lithium hydroxide and 0.003 g of carbon nanotubes in a mass ratio of 100:5:1, place them in a mortar and grind them for 10 min to mix them evenly to obtain a precursor;

[0059] S2. The precursor is placed on a carrier carbon paper of a Joule heat shock device, connected to a positive electrode and a negative electrode respectively through wires, and subjected to vacuum treatment for 10 minutes. The power supply in the Joule heat treatment device is turned on, the current is set to 200A, the voltage is set to 40V, and the precursor on the carbon paper is subjected to heat shock treatment. The single heat shock treatment time is 5s, the number of heat shock treatments is 1, and the temperature of the Joule heat shock treatment is 750°C to obtain disproportionated silicon dioxide.

[0060] Example 6

[0061] The preparation method of disproportionated silicon dioxide in this embodiment comprises the following steps:

[0062] S1. Weigh 0.3 g of silicon dioxide, 0.009 g of lithium hydroxide and 0.003 g of carbon nanotubes in a mass ratio of 100:3:1, place them in a mortar and grind them for 10 min to mix them evenly to obtain a precursor;

[0063] S2. The precursor is placed on a carrier carbon paper of a Joule heat shock device, connected to a positive electrode and a negative electrode respectively through wires, and subjected to vacuum treatment for 10 minutes. The power supply in the Joule heat treatment device is turned on, the current is set to 200A, and the voltage is set to 40V. The precursor on the carbon paper is subjected to heat shock treatment. The single heat shock treatment time is 0.1s, the number of heat shock treatments is 3 times, and the temperature of the Joule heat shock treatment is 1200°C to obtain disproportionated silicon dioxide.

[0064] Example 7

[0065] The preparation method of disproportionated silicon dioxide in this embodiment comprises the following steps:

[0066] S1. Weigh 0.3 g of silicon dioxide, 0.012 g of lithium hydroxide and 0.003 g of carbon nanotubes in a mass ratio of 100:4:1, place them in a mortar and grind them for 10 min to mix them evenly to obtain a precursor;

[0067] S2. The precursor is placed on a carrier carbon paper of a Joule heat shock device, connected to a positive electrode and a negative electrode respectively through wires, and subjected to vacuum treatment for 10 minutes. The power supply in the Joule heat treatment device is turned on, the current is set to 200A, and the voltage is set to 40V. The precursor on the carbon paper is subjected to heat shock treatment. The single heat shock treatment time is 0.1s, the number of heat shock treatments is 3 times, and the temperature of the Joule heat shock treatment is 1200°C to obtain disproportionated silicon dioxide.

[0068] Example 8

[0069] The preparation method of disproportionated silicon dioxide in this embodiment comprises the following steps:

[0070] S1. Weigh 0.3 g of silicon dioxide, 0.015 g of lithium hydroxide and 0.006 g of carbon nanotubes in a mass ratio of 100:5:2, place them in a mortar and grind them for 10 min to mix them evenly to obtain a precursor;

[0071] S2. The precursor is placed on a carrier carbon paper of a Joule heat shock device, connected to a positive electrode and a negative electrode respectively through wires, and subjected to vacuum treatment for 10 minutes. The power supply in the Joule heat treatment device is turned on, the current is set to 200A, and the voltage is set to 40V. The precursor on the carbon paper is subjected to heat shock treatment. The single heat shock treatment time is 0.1s, the number of heat shock treatments is 3 times, and the temperature of the Joule heat shock treatment is 1200°C to obtain disproportionated silicon dioxide.

[0072] Example 9

[0073] The preparation method of disproportionated silicon dioxide in this embodiment comprises the following steps:

[0074] S1. Weigh 0.3 g of silicon dioxide, 0.015 g of lithium aluminum hydride, and 0.003 g of carbon nanotubes in a mass ratio of 100:5:1, place them in a mortar, grind them for 10 min, and mix them evenly to obtain a precursor;

[0075] S2. The precursor is placed on a carrier carbon paper of a Joule heat shock device, connected to a positive electrode and a negative electrode respectively through wires, and subjected to vacuum treatment for 10 minutes. The power supply in the Joule heat treatment device is turned on, the current is set to 200A, and the voltage is set to 40V. The precursor on the carbon paper is subjected to heat shock treatment. The single heat shock treatment time is 0.1s, the number of heat shock treatments is 3 times, and the temperature of the Joule heat shock treatment is 1200°C to obtain disproportionated silicon dioxide.

[0076] Example 10

[0077] The preparation method of disproportionated silicon dioxide in this embodiment comprises the following steps:

[0078] S1. Weigh 0.3 g of silicon dioxide, 0.015 g of lithium aluminum hydride, and 0.003 g of carbon nanotubes in a mass ratio of 100:5:1, place them in a mortar, grind them for 10 min, and mix them evenly to obtain a precursor;

[0079] S2. The precursor is placed in a microwave heating device and heated in a microwave oven for 60 seconds with a power set to 1000 W to obtain disproportionated silicon dioxide.

[0080] Comparative Example 1

[0081] The difference between this comparative example and experimental example 1 is that the original silicon monoxide material is not subjected to any treatment.

[0082] Comparative Example 2

[0083] The difference between this comparative example and experimental example 1 is that silicon dioxide is prepared without adding a disproportionation initiator. The preparation method comprises the following steps:

[0084] S1. Weigh 0.3 g of silicon oxide;

[0085] S2. Place silicon 2 oxide on a carrier carbon paper of a thermal shock device, connect it to a positive electrode and a negative electrode respectively through wires, perform vacuum treatment for 10 minutes, turn on the power supply in the Joule thermal treatment device, set the current to 200A, and the voltage to 40V, perform high-temperature thermal shock treatment on the precursor on the carbon paper, the single thermal shock treatment time is 0.1s, the number of thermal shock treatments is 3 times, and the temperature of the Joule thermal shock treatment is 1200°C to obtain disproportionated silicon 2 oxide.

[0086] Comparative Example 3

[0087] The difference between this comparative example and Example 1 is that the disproportionated silicon oxide is prepared by conventional heating method. The preparation method comprises the following steps:

[0088] S1. Weigh 0.3 g of silicon dioxide, 0.015 g of lithium hydroxide and 0.003 g of carbon nanotubes in a mass ratio of 100:5:1, place them in a mortar and grind them for 10 min to mix them evenly to obtain a precursor;

[0089] S2. Sinter the precursor in a nitrogen atmosphere, raise the temperature to 950° C. at a rate of 5° C. / min, keep the temperature for 5 hours, and obtain disproportionated silicon dioxide after cooling.

[0090] Comparative Example 4

[0091] The difference between this comparative example and experimental example 1 is that the addition of lithium hydroxide is omitted.

[0092] Comparative Example 5:

[0093] The difference between this comparative example and experimental example 1 is that the addition of carbon nanotubes is omitted.

[0094] Effect verification test example

[0095] 1. Evaluation of whether disproportionation reaction occurs

[0096] Test samples: Example 1, Comparative Example 1

[0097] Test methods: XRD, XPS, TEM

[0098] Test results:

[0099] (1) X-ray diffraction pattern (such as Figure 2 ) It can be seen that in Example 1, diffraction peaks of silicon crystals appeared at 28°, 47° and 56°, proving the existence of silicon grains and the occurrence of disproportionation reaction.

[0100] (2) XPS spectrum (such as Figure 3 ) It can be seen that there is no Si nanocrystal on the surface of Comparative Example 1. After Joule heat shock, Si nanocrystals are generated on the surface of the sample of Example 1, proving the occurrence of disproportionation reaction.

[0101] (3) There are no obvious crystalline particles in the TEM image of Comparative Example 1, showing a typical amorphous structure of silicon monoxide, such as Figure 4 (a) shown; and Figure 4It can be observed in (be) that Example 1 has obvious small and dense silicon grains, the size of which is about 2 nm, distributed inside the amorphous silicon oxide matrix. In addition, the selected area electron diffraction image can also clearly see the diffraction rings of Si (111) (002) (311).

[0102] 2. Evaluation of the crystallinity of silicon nanocrystals

[0103] Test samples: Example 1, Example 2, Example 3, Example 4;

[0104] Test method: The strength of the crystallinity of silicon nanocrystals is evaluated by the peak intensity ratio of the differential capacitance curve. Figure 5 The (dQ / dV) curve of the first charge of the anode between 0.01-2 V is shown, with distinct peaks corresponding to specific lithiation stages. The peak in region I (0.1-0.3 V) corresponds to Li 3.5 The transition from Si to Li2Si, the peak in region I (0.3-0.6 V) corresponds to Li 2.0 The transition from Si to Si. Therefore, the ratio of the peak intensities of 0.45V to 0.28V can be used as an evaluation of the crystallinity of the generated nano-silicon.

[0105] Table 1 Evaluation of crystallinity

[0106]

[0107]

[0108] As shown in Table 1 above, Example 1 has the highest peak intensity ratio and the strongest silicon domain crystallinity. (In Example 5, crystalline SiO2 is generated and has lost its electrochemical activity.)

[0109] 3. Half-cell electrochemical performance test

[0110] Test samples: Example 1, Example 2, Example 3, Example 4, Comparative Example 1 and Comparative Example 2;

[0111] Test method: Prepare the negative electrode sheet and button cell as follows:

[0112] (1) Modified silicon dioxide negative electrode material: Super P: PAA = 80:10:10, distilled water is used as a solvent to prepare a slurry, and the slurry is coated on a copper foil with a thickness of 100 μm;

[0113] (2) The electrode obtained in (1) was transferred to an oven and dried at 60°C for 12 h;

[0114] (3) The dried electrode was cut into discs with a diameter of 12 mm using a cutting machine, and the discs were transferred to the glove box for lithium battery assembly. The assembly order from bottom to top is CR2025 negative electrode shell, lithium sheet, diaphragm, commercial electrolyte (formula 1MLiPF6 in EC:EMC:DMC=1:1:1 10%FEC), electrode, gasket, spring, CR2025 positive electrode shell. The button battery was electrochemically tested in the voltage range of [0.01V, 1.5V] at a current density of 0.1C (1C=1300mA / g), and the battery was discharged first and then charged.

[0115] Test results:

[0116] The disproportionated silicon oxide prepared by the present invention is used as the negative electrode material, which has good comprehensive electrochemical properties, such as Figure 6 As shown, the first charge and discharge efficiency of Example 1 is 72%, the 100-cycle cycle capacity retention rate is 98.4%, and the cycle capacity can be stabilized at 1450mAh / g. The first charge and discharge efficiency of the negative electrode material of Comparative Example 1 is 70%, and the 100-cycle cycle capacity retention rate is only 70.1%. The first charge and discharge efficiency of the negative electrode material of Comparative Example 2 is 71%, and the 100-cycle cycle capacity retention rate is 88.6%, and the cycle capacity is stable at 1300mAh / g. Compared with the embodiments, the first irreversible capacity loss of the comparative example is larger, and the cycle performance is poor.

[0117] The half-cell chemical properties of Example 1, Example 2, Example 3 and Example 4 are compared. Figure 7 As shown, the material heat-treated in Example 1 has the best electrochemical performance, with a capacity retention rate of 88.6% after 100 cycles. Therefore, the cycle performance of the battery is closely related to the crystallinity of the Si domain. The small initial size and strong crystalline phase are conducive to reducing pulverization, obtaining a larger capacity, and thus obtaining a more stable cycle.

[0118] In addition, the rate performance of Example 1 (see Figure 8 ) is also significantly improved. The capacity loss of Example 1 when the rate is increased is much smaller than that of Comparative Example 1. The specific capacity at 1C is still about 1400mAh / g, while that of Comparative Example 1 is only less than 800mAh / g. Moreover, after recovering to 0.1C rate, the specific capacity of Example 1 is very close to the initial specific capacity of 0.1C. In sharp contrast, Comparative Example 1 has obvious capacity attenuation, indicating that Example 1 does not suffer obvious structural damage or loss of active materials under high-rate charge and discharge, which is better than Comparative Example 1. Figure 1 and Figure 4It shows that the silicon oxide negative electrode material modified by Joule heat thermal shock forms tiny silicon grains inside the amorphous silicon oxide phase by inducing a controllable disproportionation reaction, thereby inhibiting the volume expansion during the charge and discharge process. In addition, after the addition of carbon nanotubes, the nanotubes can wrap the active particles and maintain in situ stabilization during the lithium insertion and deintercalation process, effectively preventing the particles from breaking and falling off, thereby significantly improving the cycle and rate performance.

[0119] Fig. 9 The half-cell data of Example 10, Example 1 and Comparative Example 3 are compared, and Example 1 has a higher specific capacity and a more stable cycle, indicating that different heat treatment methods have a greater impact on the performance of silicon dioxide materials.

[0120] 4. Synergistic crystallization of lithium source additives

[0121] Test samples: Example 1, Comparative Example 4

[0122] Test method: The strength of the crystallinity of silicon nanocrystals before and after the addition of lithium source additives is evaluated by the peak intensity ratio of the differential capacitance curve; the electrochemical performance is evaluated by assembling a half-cell test.

[0123] Table 2 Evaluation of crystallinity before and after adding lithium source additives

[0124] condition 0.45 / 0.28 peak intensity ratio average No lithium salt additives 0.68665 Add lithium salt additive 0.71464

[0125] It can be seen from Table 2 above that the peak intensity ratio of Example 1 is higher than that of Comparative Example 4, and has stronger silicon domain crystallinity.

[0126] The half-cell chemical properties of Example 1 and Comparative Example 4 are compared. Fig.10 As shown, the lithium salt additive and thermal shock in Example 1 act synergistically to induce the disproportionation reaction, making it easier to generate nano-silicon, thereby exerting a greater capacity advantage and better cycle stability.

[0127] 5. Conductive network function of CNT

[0128] Test samples: Example 1, Comparative Example 5

[0129] Test method: The electrochemical performance was evaluated by assembling half-cell tests.

[0130] Test results: Fig.11 As shown, Example 1 has higher capacity utilization and cycle stability, and the half-cell capacity retention rate increases from 88.6% to 98.4% after adding CNTs in 100 cycles. This is because after adding CNTs, the nanotubes can wrap the active particles and maintain in-situ stabilization during the lithium insertion and extraction process, effectively preventing the particles from breaking and falling off.

[0131] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a high-performance composite negative electrode material based on bulk silicon nanocrystals, characterized in that: The following steps are involved: (1) weighing silicon oxide powder, lithium source additive and thermal conductive network material, grinding and mixing to obtain a precursor mixture; (2) placing the precursor mixture on a carrier, performing a high-temperature disproportionation reaction, and cooling to room temperature to obtain a modified silicon oxide composite powder, which is the target product.

2. The method for preparing a high-performance composite negative electrode material based on bulk silicon nanocrystals according to claim 1, characterized in that: The lithium source additive is selected from one or more of LiOH·H2O, LiH, LiAlH4 and LiBH4.

3. The method for preparing a high-performance composite negative electrode material based on bulk silicon nanocrystals according to claim 1, characterized in that: The heat-conducting network material is one or more of carbon nanotubes, boron nitride, diamond or silicon carbide.

4. The method for preparing a high-performance composite negative electrode material based on bulk silicon nanocrystals according to claim 1, characterized in that: The mass ratio of silicon oxide powder, lithium source additive and thermal conductive network material is (10-40):1:(0.05-2).

5. The method for preparing a high-performance composite negative electrode material based on bulk silicon nanocrystals according to claim 1, characterized in that: The high temperature disproportionation reaction is carried out under vacuum.

6. The method for preparing a high-performance composite negative electrode material based on bulk silicon nanocrystals according to claim 1, characterized in that: The carrier is one of a graphite sheet and a carbon paper.

7. The method for preparing a high-performance composite negative electrode material based on bulk silicon nanocrystals according to claim 1, characterized in that: The heating method of the high temperature disproportionation reaction is one or more of laser induced heating, magnetic induction heating, plasma heating, Joule heat thermal shock and microwave heating.

8. The method for preparing a high-performance composite negative electrode material based on bulk silicon nanocrystals according to claim 7, characterized in that: When the heating method is microwave heating, the power of microwave heating is 900-1800W, and the heating time is 5s-3min; When the heating method is Joule heat thermal shock, the number of Joule heat thermal shock treatments is 1 to 10 times, the single time is 0.05 to 5 seconds, and the temperature is 700 to 1800°C.

9. A high-performance composite negative electrode material based on bulk silicon nanocrystals, which is prepared based on the preparation method according to any one of claims 1 to 8.

10. Use of the high-performance composite negative electrode material based on bulk silicon nanocrystals as claimed in claim 9 in the negative electrode of a lithium-ion battery.

Citation Information

Patent Citations

  • SiO composite negative electrode material for lithium ion battery and preparation method thereof

    CN108987732A

  • A high-energy silicon-containing lithium battery and a preparation method thereof-

    CN109244386A

  • A kind of thiolated polyacrylic acid aqueous polymer binder for silicon-based negative electrode of lithium ion battery and its preparation method and application

    CN116759581B

  • Ellipsoidal SiOx / graphite cathode composite material and preparation method and application thereof

    CN106410177A

  • Composite silicon-based material, negative electrode material and preparation method thereof and lithium ion battery

    CN110600720A